Thermal insulation material for promoting low-temperature activity expression of anaerobic ammonium oxidation bacteria and preparation method of thermal insulation material
By using polyacrylonitrile fibers and thermally conductive carbon materials on the carrier of anaerobic ammonia oxidizing bacteria, the problem of inhibition of growth and metabolism under low temperature conditions is solved, and metabolic activity and treatment efficiency are improved. Suitable for wastewater treatment in cold areas.
Patent Information
- Application Number
- CN202411510765.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The growth and metabolism of anaerobic ammonia oxidation technology under low temperature conditions is inhibited, resulting in a decrease in ammonia oxidation efficiency, limiting its application in actual engineering.
Using insulation materials loaded with polyacrylonitrile fibers and surface grafted thermally conductive carbon materials on polyurethane sponges, the heat on the surface of the carrier is maintained through the thermal conduction of thermally conductive carbon materials and the thermal insulation properties of polyacrylonitrile, and help anaerobic ammonia oxidizing bacteria resist low-temperature impact. .
It improves the metabolic activity and growth rate of anaerobic ammonia oxidizing bacteria at low temperatures, improves the efficiency and stability of wastewater treatment, and is suitable for wastewater biological treatment processes in cold areas or in areas with seasonal temperature changes.
Smart Images

Figure CN119391043A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sewage treatment, and in particular to a heat-insulating material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria and a preparation method thereof. Background Art
[0002] In recent years, anaerobic ammonium oxidation technology has emerged as an innovative biological denitrification method and is internationally recognized as the most economical and efficient green denitrification technology. In an oxygen-deficient environment, autotrophic anaerobic ammonium oxidizing bacteria (AnAOB) use nitrite (NO2 - -N) as an electron acceptor, ammonia nitrogen (NH4 + -N) as an electron donor, simultaneously removing these two forms of nitrogen and converting them into nitrogen gas. Compared with traditional methods, anaerobic ammonia oxidation has the advantages of no need for aeration, low energy consumption, no need to add additional organic carbon sources, and small residual sludge production. It can effectively save operating costs and reduce the risk of secondary pollution. However, this technology usually needs to be carried out at a higher temperature of 30 to 35°C to ensure the normal growth and metabolism of AnAOB bacteria. When the temperature drops below 15°C, the growth and metabolism of AnAOB bacteria will be inhibited, the activity will be reduced, the ammonia oxidation efficiency will decrease, and even the process will collapse, which greatly limits the application of anaerobic ammonia oxidation technology in actual engineering.
[0003] At present, researchers and engineers at home and abroad have tried various methods to improve the metabolic activity and growth rate of anaerobic ammonia-oxidizing bacteria at low temperatures, such as local heating, external electric field enhancement and external magnetic field enhancement, but the effects of these methods are still not satisfactory.
[0004] New carbon materials, such as graphene oxide and graphite carbon nitride, have attracted much attention due to their high specific surface area and rich surface functional groups. The thermal conduction of these materials is mainly achieved through the thermal vibration of lattice atoms, with a thermal conductivity of up to 3000-5000 W / (m·K). They can maintain good thermal conductivity under different temperature conditions and transfer heat quickly and effectively, so they can be used as efficient thermal interface materials. In addition, the carbon atoms in these carbon materials are sp 2 Hybridization forms a continuous π-bond network structure, and charge carriers can move freely along its two-dimensional plane to form a highly conductive π-electron band. Therefore, this type of material also has the property of promoting electron transfer between microbial species. As a synthetic fiber, polyacrylonitrile fiber is widely used in thermal insulation materials due to its excellent thermal insulation performance. Polyurethane is favored for its excellent chemical corrosion resistance. my country is a major polyurethane trading and production country, and a large amount of waste polyurethane plastics and textiles are produced every year. Among them, the polyurethane porous sponge has a large specific surface area, which is easy for microorganisms to attach. Its uniform and high porosity ensures the smooth mass transfer inside and outside the carrier, providing an ideal growth environment for microorganisms. Summary of the invention
[0005] In view of this, the present invention provides a thermal insulation material and a preparation method for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria. The present invention uses thermal conductive carbon materials and polyacrylonitrile fibers to retain external heat in a polyurethane carrier. When the external environment temperature drops sharply, the heat retained by the carrier can help the anaerobic ammonia-oxidizing bacteria on the surface of the carrier effectively resist the impact of low temperature, thereby improving the metabolic activity of the anaerobic ammonia-oxidizing bacteria on the surface of the carrier at low temperatures.
[0006] A thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, the thermal insulation material comprising polyacrylonitrile fibers loaded on a polyurethane sponge and a surface-grafted thermally conductive carbon material.
[0007] Preferably, the thermal insulation material includes the following raw materials in parts by weight: 10 to 20 parts of polyurethane sponge, 7 to 15 parts of thermal conductive carbon material, 10 to 15 parts of acrylonitrile, 1 to 3 parts of methyl acrylate, 5 to 10 parts of butyl acrylate, 30 to 45 parts of coupling agent, 5 to 10 parts of initiator, 25 to 30 parts of solvent a, and 20 to 30 parts of solvent b.
[0008] Preferably, the thermally conductive carbon material includes at least one of graphite-phase carbon nitride, graphene, and graphene oxide.
[0009] Preferably, the coupling agent includes at least one of monoalkoxy titanate, chelate titanate, epoxy silane, mercapto silane and amino silane.
[0010] Preferably, the initiator includes at least one of benzoyl peroxide, ammonium persulfate, azobisisobutyronitrile, ammonium persulfate and N,N-dimethylaniline.
[0011] Preferably, the solvent a includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, ethyl nitrate, and concentrated nitric acid.
[0012] Preferably, the solvent b is a miscible product of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:1.
[0013] The present invention also provides a method for preparing the thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, comprising the following steps:
[0014] (1) Preparation of PU / PAN material: Initiator, solvent a, acrylonitrile and methyl acrylate are placed in a reaction vessel in proportion, heated in a water bath at 50-70° C., stirred for 12-15 h under an inert gas atmosphere, and then polyurethane sponge is added. After stirring for a period of time, the sponge is taken out and vacuum dried to constant weight to obtain PU / PAN material;
[0015] (2) Preparation of PU / PC material: Place thermal conductive carbon material, coupling agent and butyl acrylate in solvent b according to proportion, stir for 10-30 min at room temperature, then add the PU / PAN material described in step (1), take out after stirring for a period of time, and vacuum dry to constant weight to obtain PU / PC material.
[0016] Preferably, after stirring for a period of time in step (1) and step (2), the temperature of the reaction container is lowered to room temperature, the solid and liquid are separated, and the polyurethane sponge solid is washed alternately with anhydrous ethanol and deionized water for 3-5 times.
[0017] Preferably, the drying temperature in step (1) and step (2) is 60-80°C.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention utilizes in-situ grafting technology to combine the thermal insulation material polyacrylonitrile (PAN) with the polyurethane (PU) porous bio-carrier, and simultaneously deposits the thermal conductive carbon material on the surface, which not only simplifies the synthesis but also ensures the stability and durability of the carrier.
[0020] (2) The surface of the PU / PAN-C carrier prepared in the present invention is deposited with a graphite structure high thermal conductivity material, which can quickly conduct heat from the environment to the material surface. The heat is retained by the thermal insulation material, effectively alleviating the low-temperature impact of the biofilm ecology on the carrier surface, and enhancing its adaptability to environmental stresses such as low temperature, thereby improving the wastewater treatment efficiency and stability.
[0021] (3) Graphite-phase carbon material is deposited on the surface of the PU / PAN-C carrier prepared in the present invention. Its two-dimensional continuous structure constitutes a π-bond network, in which electrons move quickly and freely, thereby enhancing the interspecies electron transfer of microorganisms attached to the carrier surface, contributing to the construction of symbiotic bacterial communities, and promoting the stability of the biological system.
[0022] (4) The PU / PAN-C carrier prepared in the present invention has a macroporous interpenetrating structure and an excellent fluidization effect, which is beneficial to the diffusion and mass transfer of ions in water.
[0023] (5) The biological carrier with high thermal conductivity and heat preservation properties prepared by the present invention is particularly suitable for wastewater biological treatment processes in cold areas or areas with seasonal temperature changes. It can quickly conduct and store environmental heat, effectively alleviate the impact of microorganisms on the surface of the carrier on environmental temperature changes, thereby significantly improving the treatment efficiency and stability of wastewater biological treatment processes under low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Graph showing the change in water environment temperature of the carrier in the embodiments of the present invention and the comparative examples.
[0025] Figure 2 It is the SEM characterization picture of the carrier in the embodiment of the present invention and the comparative example.
[0026] Figure 3 It is a graph of the denitrification performance of the anaerobic ammonia oxidation system of the carrier prepared in the examples and comparative examples of the present invention.
[0027] Figure 4 It is a SAA variation diagram of the anaerobic ammonia oxidation system of the carrier prepared in the examples and comparative examples of the present invention. DETAILED DESCRIPTION
[0028] A thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, the thermal insulation material comprising polyacrylonitrile fibers loaded on a polyurethane sponge and a surface-grafted thermally conductive carbon material.
[0029] In the present invention, the thermal insulation material comprises the following raw materials by weight: 10-20 parts of polyurethane sponge, 7-15 parts of thermal conductive carbon material, 10-15 parts of acrylonitrile, 1-3 parts of methyl acrylate, 5-10 parts of butyl acrylate, 30-45 parts of coupling agent, 5-10 parts of initiator, 25-30 parts of solvent a, and 20-30 parts of solvent b;
[0030] Further preferably, the thermal insulation material comprises the following raw materials, by weight: 15-20 parts of polyurethane sponge, 10-15 parts of thermal conductive carbon material, 10-12 parts of acrylonitrile, 2-3 parts of methyl acrylate, 8-10 parts of butyl acrylate, 35-45 parts of coupling agent, 8-10 parts of initiator, 28-30 parts of solvent a, and 28-30 parts of solvent b; more preferably, the thermal insulation material comprises the following raw materials, by weight: 15 parts of polyurethane sponge, 11 parts of thermal conductive carbon material, 12 parts of acrylonitrile, 2 parts of methyl acrylate, 8 parts of butyl acrylate, 38 parts of coupling agent, 8 parts of initiator, 30 parts of solvent a, and 30 parts of solvent b.
[0031] In the present invention, the thermally conductive carbon material includes at least one of graphite-phase carbon nitride, graphene, and graphene oxide. More preferably, the thermally conductive carbon material is graphite-phase carbon nitride.
[0032] In the present invention, the coupling agent includes at least one of monoalkoxy titanate, chelate titanate, epoxy silane, mercapto silane and amino silane.
[0033] In the present invention, the initiator includes at least one of benzoyl peroxide, ammonium persulfate, azobisisobutyronitrile, ammonium persulfate and N,N-dimethylaniline.
[0034] In the present invention, the solvent a includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, ethyl nitrate and concentrated nitric acid.
[0035] In the present invention, the solvent b is a miscible product of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1-1.2:1-1.5, and more preferably, the solvent b is a miscible product of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:1.
[0036] The present invention also provides a method for preparing the thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, comprising the following steps:
[0037] (1) Preparation of PU / PAN material: Initiator, solvent a, acrylonitrile and methyl acrylate are placed in a reaction vessel in proportion, heated in a water bath at 50-70° C., stirred for 12-15 h under an inert gas atmosphere, and then polyurethane sponge is added. After stirring for a period of time, the sponge is taken out and vacuum dried to constant weight to obtain PU / PAN material;
[0038] (2) Preparation of PU / PC material: Place thermal conductive carbon material, coupling agent and butyl acrylate in solvent b according to proportion, stir for 10-30 min at room temperature, then add the PU / PAN material described in step (1), take out after stirring for a period of time, and vacuum dry to constant weight to obtain PU / PC material.
[0039] In the present invention, the acrylonitrile in step (1) is the main raw material and the first monomer for synthesizing polyacrylonitrile; methyl acrylate as the second monomer has excellent adhesion and good chemical stability, which can promote the synthesis of polyacrylonitrile and make it have excellent performance.
[0040] In the present invention, the heat-conducting carbon material described in step (2) is deposited on the surface of PU / PAN, and with its excellent thermal conductivity, it quickly transfers the heat in the water to the surface of the synthetic polymer carrier. The PAN on the surface of the carrier has heat-insulating properties, which retains the heat on the surface of the carrier, and provides the required temperature environment for the bacterial biofilm on the surface. When the ambient temperature decreases, on the one hand, the porous structure of the carrier effectively avoids the impact of low temperature on the microorganisms; on the other hand, the temperature retained by PAN continues to act, further buffering the adverse effects of changes in external environmental temperature, and effectively alleviating the impact of low temperature shock on the biological system. At the same time, the presence of π bonds in this two-dimensional carbon structure can effectively promote electron transfer between microbial species, promote the construction of symbiotic ecology and the coordinated metabolism of functional microorganisms, and help the carrier system cope with adverse environmental changes.
[0041] In the present invention, the butyl acrylate in step (2) can be used as an adhesive in the process of modifying the material due to its good bonding properties. In addition, due to its excellent corrosion resistance, it can effectively improve the durability of the polyacrylonitrile fiber.
[0042] In the present invention, after stirring for a period of time in step (1) and step (2), the temperature of the reaction container is lowered to room temperature, the solid and liquid are separated, and the polyurethane sponge solid is washed 3-5 times alternately with anhydrous ethanol and deionized water.
[0043] In the present invention, the drying temperature in step (1) and step (2) is 60-80°C; more preferably, the drying temperature in step (1) and step (2) is 60°C, 70°C, or 80°C.
[0044] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0045] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the raw materials and auxiliary agents are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0046] Example 1
[0047] A method for preparing a thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, the specific steps are as follows:
[0048] (1) Preparation of PU / PAN material: 8 parts by weight of azobisisobutyronitrile, 30 parts by weight of N,N-dimethylacrylamide, 12 parts by weight of acrylonitrile monomer and 2 parts by weight of methyl acrylate were added to a three-necked flask, the three-necked flask was placed in a 60°C water bath, stirred for 14 hours under a nitrogen atmosphere, 15 parts by weight of polyurethane sponge was added, the stirring was continued for 40 minutes, and the heating and stirring were stopped. The three-necked flask was taken out of the water bath, cooled to room temperature, the polyurethane sponge was taken out, and washed alternately with anhydrous ethanol and deionized water for 3 times. The solid was dried in a vacuum drying oven at 80°C to constant weight to obtain a PU / PAN material;
[0049] (2) Preparation of PU / PC material: 11 parts by weight of graphite carbon nitride, 38 parts by weight of epoxysilane and 8 parts by weight of butyl acrylate were added to 30 parts by weight of 50% N,N-dimethylacrylamide ethanol solvent, stirred at room temperature for 20 min, and the PU / PAN material described in step (1) was added, and stirring was continued for 80 min. The polyurethane sponge was taken out, and the sponge solid was washed three times with anhydrous ethanol and deionized water alternately, and vacuum dried at 80°C to constant weight to obtain the PU / PC material.
[0050] Example 2
[0051] A method for preparing a thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, the specific steps are as follows:
[0052] (1) Preparation of PU / PAN material: 5 parts by weight of azobisisobutyronitrile, 25 parts by weight of N,N-dimethylacrylamide, 10 parts by weight of acrylonitrile monomer and 1 part by weight of methyl acrylate were added to a three-necked flask, and the three-necked flask was placed in a 50°C water bath, stirred for 12 hours under a nitrogen atmosphere, and then a polyurethane sponge was added and stirred for 30 minutes. The three-necked flask was taken out, and after the temperature of the container dropped to room temperature, the solid and liquid were separated, and the polyurethane sponge solid was washed 5 times with anhydrous ethanol and deionized water alternately, and vacuum dried at 60°C to constant weight to obtain a PU / PAN material.
[0053] (2) Preparation of PU / P-GO material: 7 parts by weight of graphene oxide, 30 parts by weight of epoxysilane and 5 parts by weight of butyl acrylate were added to 25 parts by weight of 50% N,N-dimethylacrylamide ethanol solvent, stirred at room temperature for 10 minutes, and the PU / PAN material described in step (1) was added, and stirring was continued for 60 minutes. The sponge solid was taken out, and the polyurethane sponge solid was washed alternately with anhydrous ethanol and deionized water for 5 times, and vacuum dried to constant weight to obtain the PU / P-GO material.
[0054] Example 3
[0055] A method for preparing a thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, the specific steps are as follows:
[0056] (1) Preparation of PU / PAN material: 10 parts by weight of azobisisobutyronitrile, 30 parts by weight of N,N-dimethylacrylamide, 15 parts by weight of acrylonitrile monomer and 3 parts by weight of methyl acrylate were added to a three-necked flask, the three-necked flask was placed in a 60°C water bath, stirred for 15 hours under a nitrogen atmosphere, 20 parts by weight of polyurethane sponge was added, the stirring was continued for 50 minutes, and the heating and stirring were stopped. The three-necked flask was taken out of the water bath, cooled to room temperature, the polyurethane sponge was taken out, and washed alternately with anhydrous ethanol and deionized water for 4 times. The solid was dried in a 70°C vacuum drying oven to constant weight to obtain a PU / PAN material;
[0057] (2) Preparation of PU / P-1LG material: 15 parts by weight of single-layer graphene, 45 parts by weight of epoxysilane and 10 parts by weight of butyl acrylate were added to 35 parts by weight of 50% N,N-dimethylacrylamide ethanol solvent, stirred at room temperature for 30 minutes, and the PU / PAN material described in step (1) was added, and stirring was continued for 120 minutes. The polyurethane sponge solid was taken out, and the sponge solid was washed alternately with anhydrous ethanol and deionized water for 5 times, and vacuum dried at 70°C to constant weight to obtain the PU / P-1LG material.
[0058] Comparative Example 1
[0059] The difference from Example 1 is that no graphite phase carbon nitride is added during the preparation of the thermal insulation material, and the remaining steps are consistent with Example 1, that is, the thermal insulation material of Comparative Example 1 is a PU / PAN carrier.
[0060] Comparative Example 2
[0061] The difference from Example 1 is that polyacrylonitrile is not added during the preparation of the thermal insulation material, and the remaining steps are consistent with Example 1, that is, the thermal insulation material of Comparative Example 2 is a PU / C carrier.
[0062] Comparative Example 3
[0063] The difference from Example 1 is that polyacrylonitrile and graphite-phase carbon nitride are not added during the preparation of the thermal insulation material, and the remaining steps are consistent with Example 1, that is, the thermal insulation material of Comparative Example 3 is a PU carrier.
[0064] The performance of the thermal insulation materials provided in Examples 1-3 and Comparative Examples 1-3 is tested below.
[0065] 1) Weigh a certain amount of the thermal insulation material carriers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 and place them in 100 mL beakers respectively, put them in a 35°C constant temperature water bath and stir for 60 min, take out the carriers and place them in a 17°C water environment, insert the temperature probe into the middle of the sponge at intervals of 20 min, and measure the temperature change inside the sponge. The results are as follows: Figure 1 .
[0066] Depend on Figure 1 It can be seen that the temperature of the unmodified polyurethane sponge (Comparative Example 3) drops significantly faster than that of the modified group when it undergoes a cooling process; in the modified group, the resistance of the PU / PAN material prepared in Comparative Example 1 and the PU / C material prepared in Comparative Example 2 to low temperature shock is significantly better than that of Comparative Example 3, but the effect is still not ideal. Further optimization, adding new carbon materials and PAN materials at the same time, that is, the materials prepared in Examples 1 to 3, have good thermal insulation performance when facing a sudden drop in temperature, and can maintain the normal growth and metabolism of AnAOB bacteria.
[0067] The PU / PAN-C material prepared from the graphite phase carbon nitride thermal conductive material in Example 1 has similar thermal insulation performance to the PU / PAN-1LG material prepared from the graphene oxide in Example 2 and the single-layer graphene in Example 3. Based on cost considerations, the carrier prepared in Example 1 is preferably used as the experimental object.
[0068] 2) SEM characterization of the carrier before and after modification Figure 2 shown.
[0069] Among them, Figure a is a PU carrier (Comparative Example 3), with a smooth surface and rich pores in the cavity; Figure b is a PU / PAN carrier (Comparative Example 1), with a rougher surface than the PU carrier and a smaller pore size, and a large number of evenly distributed particles can be observed, which is presumed to be embedded PAN; Figure c is a PU-C carrier (Comparative Example 2), with a smooth surface, more small pores, and flake carbon nitride physically deposited on the surface of the PU carrier, but after placing it in deionized water and stirring for 40 minutes, the COD value detected is low, and almost no reducing substances fall off, indicating that the load is relatively firm; Figure d is a PU / PC carrier (Example 1), with a relatively rough surface and rich in small pores, which is conducive to the initial adhesion and enrichment of microorganisms; particles and layered substances are observed on the surface of the material at the same time, indicating that PAN and carbon nitride are successfully loaded. Figures e and f are PU / P-GO carriers (Example 2) and PU / P-1LG carriers (Example 3), respectively, with rough surfaces, and a large number of particles and monolayer flake substances can be observed, indicating that PAN and graphene are successfully loaded.
[0070] 3) The denitrification performance of the anaerobic ammonium oxidation system with different carriers is shown in the figure below Figure 4 shown.
[0071] The experiment used 6 cylindrical plexiglass reactors R1, R2, R3, R4, R5 and R6 with an effective volume of 1.6L, among which R1 was added with ordinary unmodified PU carrier of comparative example 3, R2 was added with PU / PC carrier prepared in Example 1, R3 was added with PU / P-GO carrier prepared in Example 2, R4 was added with PU / P-1LG carrier prepared in Example 3, R5 was added with PU / PAN carrier prepared in comparative example 1, and R6 was added with PU-C carrier prepared in comparative example 2, and the filling rate was 22%.
[0072] The inoculum sludge concentration is 2.1g / L, and the specific activity (SAA) is 0.14gN / (gSS·d) of anaerobic ammonium oxidation sludge. Artificial water distribution is adopted: NH4Cl is added to the influent (providing NH4 + ), NaNO2 (provides NO2 - ); NaHCO3 was added to adjust the alkalinity and maintain the pH at 7.5-8.0; anhydrous sodium sulfite was added to make the inlet DO concentration lower than 0.2 mg / L. The reactor was operated for a total of 48 days, including three stages. The specific operating parameters are shown in Table 1.
[0073] In the first stage (1-21 days), the SBR mode was used to allow the anaerobic ammonium oxidizing bacteria to attach to the carrier and replicate to complete the initial biofilm formation; in the second stage (22-35 days), the hydraulic retention time was reduced and the water was continuously in and out to promote the rapid growth of the anaerobic ammonium oxidizing biofilm; in the third stage (36-48 days), the system temperature was reduced to 15°C to explore the effects of different carriers on the activity of anaerobic ammonium oxidizing bacteria at lower temperatures.
[0074] Table 1 Experimental operating parameters
[0075]
[0076] Note: HRT stands for hydraulic retention time
[0077] Depend on Figure 3 It can be seen that the reactor was operated at 35°C for 21 days (stage I), and the average removal rates of ammonia nitrogen, nitrite nitrogen, and total nitrogen in the reactor inlet were 85.7%, 97.8%, and 87.7%, respectively, with good denitrification performance. During the 22nd to 48th day of operation (stages II and III), the reactor was cooled down, and the entire process was operated in a continuous flow, maintaining a constant HRT (22.22h), and the concentrations of ammonia nitrogen and nitrite nitrogen in the reactor inlet were set to 40.02±2.88mg / L and 52.52±3.30mg / L, respectively. Starting from 22d, the denitrification performance of the reactor without the carrier prepared in Examples 1 to 3 was significantly affected by temperature, especially in stage III, the average ammonia nitrogen removal rates of R1, R5 and R6 dropped to 49.03%, 54.22% and 58.49%, the average nitrite removal rates dropped to 51.04%, 54.30% and 57.68%, and the average total nitrogen removal rates dropped to 40.02%, 46.81% and 48.29%, respectively; while the total nitrogen removal rate of the reactor with the insulation carrier described in Examples 1-3 of the present invention was still maintained above 70%. After 48 days of cultivation, the carriers prepared in Comparative Examples 1 to 3 were added to the R1, R5 and R6 reactors, and SAA decreased significantly, from 0.14 gN / (gSS·d) to 0.03 gN / (gSS·d), 0.046 gN / (gSS·d) and 0.053 gN / (gSS·d), respectively; the insulation materials were added to the R2, R3 and R4 reactors, and although SAA decreased, it still maintained a high activity (0.106 gN / (gSS·d), 0.108 gN / (gSS·d) and 0.104 gN / (gSS·d), respectively). It can be seen that the carriers loaded with PAN and new carbon materials at the same time are more conducive to improving the resistance of microorganisms to low temperature in the anaerobic ammonia oxidation system, and can maintain the stable denitrification of the system (see Figure 3 and Figure 4 ).
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria, characterized in that: The thermal insulation material comprises polyacrylonitrile fibers loaded on a polyurethane sponge and a surface-grafted thermal conductive carbon material.
2. The thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 1, characterized in that: The thermal insulation material comprises the following raw materials in parts by weight: 10 to 20 parts of polyurethane sponge, 7 to 15 parts of thermal conductive carbon material, 10 to 15 parts of acrylonitrile, 1 to 3 parts of methyl acrylate, 5 to 10 parts of butyl acrylate, 30 to 45 parts of coupling agent, 5 to 10 parts of initiator, 25 to 30 parts of solvent a, and 20 to 30 parts of solvent b.
3. The thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to any one of claims 1 or 2, characterized in that: The thermally conductive carbon material includes at least one of graphite-phase carbon nitride, graphene, and graphene oxide.
4. The thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 2, characterized in that: The coupling agent includes at least one of monoalkoxy titanate, chelate titanate, epoxy silane, mercapto silane and amino silane.
5. The thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 2, characterized in that: The initiator includes at least one of benzoyl peroxide, ammonium persulfate, azobisisobutyronitrile, ammonium persulfate and N,N-dimethylaniline.
6. The thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 2, characterized in that: The solvent a includes at least one of N,N-dimethylformamide, dimethyl sulfoxide, sulfolane, ethyl nitrate and concentrated nitric acid.
7. The thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 2, characterized in that: The solvent b is a miscible product of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:
1.
8. The method for preparing a heat-insulating material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 2, characterized in that: The following steps are involved: (1) Preparation of PU / PAN material: Initiator, solvent a, acrylonitrile and methyl acrylate are placed in a reaction vessel in proportion, heated in a water bath at 50-70° C., stirred for 12-15 h under an inert gas atmosphere, and then polyurethane sponge is added. After stirring for a period of time, the sponge is taken out and vacuum dried to constant weight to obtain PU / PAN material; (2) Preparation of PU / PC material: Place thermal conductive carbon material, coupling agent and butyl acrylate in solvent b according to proportion, stir for 10-30 min at room temperature, then add the PU / PAN material described in step (1), take out after stirring for a period of time, and vacuum dry to constant weight to obtain PU / PC material.
9. The method for preparing a heat-insulating material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 8, characterized in that: After stirring for a period of time in step (1) and step (2), the temperature of the reaction container is lowered to room temperature, the solid and liquid are separated, and the polyurethane sponge solid is washed 3-5 times alternately with anhydrous ethanol and deionized water.
10. The method for preparing the thermal insulation material for promoting the low-temperature activity expression of anaerobic ammonia-oxidizing bacteria according to claim 8, characterized in that: The drying temperature in step (1) and step (2) is 60-80°C.